2021
DOI: 10.3390/microorganisms9061146
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Serum Hepatitis B Virus Pregenomic RNA Kinetics in Chronic Hepatitis B Patients Receiving Antiviral Treatment and Those Achieving HBsAg Loss

Abstract: Serum hepatitis B virus (HBV) pregenomic RNA (pgRNA) is correlated with covalently closed circular DNA. We aimed to investigate the utility of serum HBV pgRNA in chronic hepatitis B patients receiving nucleos(t)ide analogue treatment and those achieving HBsAg loss. One hundred and eighty-five patients were enrolled for studying long-term HBV pgRNA kinetics during treatment. Twenty patients achieving HBsAg loss after treatment were enrolled for examining HBV pgRNA kinetics around HBsAg loss. HBV pgRNA significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…Regarding the turning time of HBsAg and HBV pgRNA, all HBV pgRNA disappeared before or at HBsAg loss, with a lower LOD of HBV pgRNA. However, Wu et al reported that 65% of patients with HBV pgRNA had a later negative turning than HBsAg (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the turning time of HBsAg and HBV pgRNA, all HBV pgRNA disappeared before or at HBsAg loss, with a lower LOD of HBV pgRNA. However, Wu et al reported that 65% of patients with HBV pgRNA had a later negative turning than HBsAg (11).…”
Section: Discussionmentioning
confidence: 99%
“…After 9-year NA treatment, 9.9% of the patients still had detectable serum HBV pgRNA levels. Wu et al (11) reported that baseline serum HBV pgRNA alone was not sufficient to predict the trajectory of HBV pgRNA. Similarly, clinical characteristics were not significantly different between patients positive and negative for HBV pgRNA at the early stage of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…HBV RNA was extracted from 150 µL of serum using the Total RNA Extraction Miniprep System Kit according to the manufacturer’s instructions (Viogene, Taipei, Taiwan) and treated with DNase I (Thermo Fisher Scientific, Waltham, MA, USA). Isolated HBV RNA was reverse transcribed to complementary DNA using RevertAid reverse transcriptase (Thermo Fisher Scientific, Waltham, MA, USA) with an HBV specific RT primer for HBV pgRNA [ 24 ]. The complementary DNA samples were held at 4 °C before proceeding to quantitative real-time polymerase chain reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The levels of serum HBV RNA were detected by qPCR in LightCycler 480 II Real-time PCR Detection System (Roche, Mannheim, Germany) with a SYBR Green method [ 24 ]. The limit of detection of serum HBV pgRNA was 1466 copies/mL, as calculated by probit analysis [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation